The brook book : exploring the smallest streams - Arnosky, Jim. (New York : Dutton Children's Books, 2008)
Describes the many different types of plants, fish, and animals that live in or near even the smallest streams.
Includes bibliographical references.
Booklist.
Kirkus Starred.
School Library Journal.
3.7
K-3
Keywords: Animals -- Juvenile literature; Fishes -- Juvenile literature; Plants -- Juvenile literature; Rivers -- Juvenile literature; Stream ecology -- Juvenile literature; Animals; Fishes; Plants; Rivers; Animals; Fishes; Plants; Rivers